(untitled) (Bangladesh Journal of Pharmacology, 2015)
The present study was carried out to evaluate the seeds of Pennisetum glaucum for its blood pressure lowering effect in rats. Aqueous-methanolic extract of P. glaucum seeds in 250, 500 and 1000 mg/kg doses was studied in normotensive, egg-feed diet and glucose-induced hypertensive rats using non-invasive technique. The extract significantly (p?0.5 - p?0.001) decreased blood pressure and heart rate with maximum effect at 1,000 mg/kg dose. The extract was found to prevent rise in blood pressure of egg and glucose fed rats as compared to control group in 21 days study. The extract was safe in mice up to dose of 4 g/kg and sub-chronic toxicity study showed that there was no significant alterations in blood chemistry of extract treated rats. It is conceivable, therefore, that aqueous-methanolic extract of P. glaucum seeds has exerted considerable antihypertensive activity which may be due to the presence of phytochemical constituents.